Pengaruh Peluang dan Tantangan Kopi Kenangan Terhadap Gaya Hidup Gen Z Dibandingkan dengan Kedai Kopi Lain di Kota Serang - Vera Maria; Dea Firnanda; Devi Yani; Fidda Nuraini Nabilah; Riska Anggraini (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The rapid growth of the coffee business in Indonesia, especially in the city of Serang, has led to very fierce competition among coffee entrepreneurs. This requires coffee business owners to have the right strategy to be able to compete effectively. This study aims to analyze the influence of opportunities and challenges faced by Kopi Kenangan on the lifestyle of Gen Z in Serang City compared to other coffee shops. This research was conducted using a qualitative method to explore the perception of Gen Z towards the influence of opportunities and challenges offered by Kopi Kenangan compared to other coffee shops in Serang City. This study concludes that although Kopi Kenangan offers various competitive advantages, the existence of other coffee shops with their distinctive characteristics contributes to the diverse lifestyle choices of Gen Z in Serang City. These results are expected to provide input for coffee entrepreneurs in developing marketing strategies that are relevant to the needs and consumption trends of Gen Z.